Biomedical scientists' recognition and alleviation of pain and distress in laboratory rats and mice - Parkison, Valerie; Rutberg, Allen; Dizard, Jan E (Tufts Archival Research Center, 2019)
Scientific research on animals is a well-publicized ethical debate in our society. In part because of increasing attention to this issue, national legislation regarding laboratory animal welfare was created in 1966 with the Animal Welfare Act (AWA) and has been strengthened in the recent decades with its subsequent amendments, particularly the 1985 Improved Standards for Laboratory Animals. A separate law, the Health Research Extension Act, was also passed in 1985. However, research has shown that these regulations are not implemented uniformly throughout individual laboratories and institutions.; Thesis submitted for the MS in Animals and Public Policy degree.